2023
DOI: 10.3389/fnsys.2023.1129152
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disruption of memory consolidation in Drosophila

Abstract: The role of the circadian system in memory formation is an important question in neurobiology. Despite this hypothesis being intuitively appealing, the existing data is confusing. Recent work in Drosophila has helped to clarify certain aspects of the problem, but the emerging sense is that the likely mechanisms are more complex than originally conceptualized. In this report, we identify a post-training window of time (during consolidation) when the circadian clock and its components are involved in memory form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…per expression is essential for establishing 1 d memory induced by aversive olfactory learning [26]. Furthermore, as was observed in courtship LTM, Yin et al reported that light is required for the maintenance of LTM induced by aversive olfactory learning and that a clock gene other than per, vrill is also required for the consolidation of LTM induced by aversive olfactory learning [39]. These findings imply that clock genes and clock neurons play an important role in the regulation of Drosophila LTM, regardless of the learning method.…”
Section: Possible Model Of the Regulation Of Ltm Maintenance Via Lndsmentioning
confidence: 88%
“…per expression is essential for establishing 1 d memory induced by aversive olfactory learning [26]. Furthermore, as was observed in courtship LTM, Yin et al reported that light is required for the maintenance of LTM induced by aversive olfactory learning and that a clock gene other than per, vrill is also required for the consolidation of LTM induced by aversive olfactory learning [39]. These findings imply that clock genes and clock neurons play an important role in the regulation of Drosophila LTM, regardless of the learning method.…”
Section: Possible Model Of the Regulation Of Ltm Maintenance Via Lndsmentioning
confidence: 88%
“…performance by recruiting neuromodulatory pathways to optimize information processing in the brain. In flies, clock circuits play an active role in memory formation, regulate sleep and waking, and impose daily activity rhythms onto dopaminergic neurons ( 3237 ). Thus, here we examine the intricate interplay between sleep, clock circuits, and dopaminergic modulatory pathways in shaping memory formation in flies suffering catastrophic brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the behavioral criteria for sleep in mammals. As a result, research in D. melanogaster has shown not only that sleep facilitates learning in wild-type and memory-impaired flies, but also that sleep deprivation impairs the acquisition and consolidation of new memories [14,15].…”
Section: Introductionmentioning
confidence: 99%